Percepção do clima organizacional dos trabalhadores da Empresa ALFA - Scaravonatto, Victor Hugo (2023)
The economic market is getting more complex for the organizations, which should be attentive to the changes in the social context and also in the interior happenings in the daily work. In this context, using tools as organizational environment research, as the Great Place To Work (GPTW) model, it becomes fundamental to better understand the environment in the organization and to seek for solutions to eradicate the identified problems. Thus, this task objective was to analyze the perception of the organizational environment, relating the satisfaction indexes of the collaborators and stablishing relations with the rotativity tax. For that, it was done qualitative and descriptive study, using the questionnaire with closed questions based in the GPTW model, applying it to the employees and the managers, in order to get precise results. The questionnaire was adapted from Pereira (2003), including questions related to the organizational environment. It was evaluated credibility, respect, impartiality, proud and camaraderie variables. Among them, proud presented the biggest media, reaching 4.4, what shows the employees’ satisfaction with the company. Others variables, as the credibility, respect, impartiality and camaraderie reached 4.3 media, showing satisfaction, but also the need of some improvements. Among the data collected, stands out the employees express proud related to the company and the fact they are part of the team, which motivates them to keep working for years, especially because of the good work recognition. Also, because of the leaders’ competence and the treatment equality, without discrimination because of race, color, genre or function. However, even the organizational environment in a satisfactory way, some negative questions were pointed out, including the lack of celebrating in commemorative dates and the lack of autonomy in tasks execution. So, it was developed an action plan with measures to improve the organizational environment in the company.